2012
DOI: 10.1371/journal.pone.0039126
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Responses of Resistant and Susceptible Fish Clones to the Bacterial Pathogen Flavobacterium psychrophilum

Abstract: Flavobacterium psychrophilum is a bacterial species that represents one of the most important pathogens for aquaculture worldwide, especially for salmonids. To gain insights into the genetic basis of the natural resistance to F. psychrophilum, we selected homozygous clones of rainbow trout with contrasted susceptibility to the infection. We compared the transcriptional response to the bacteria in the pronephros of a susceptible and a resistant line by micro-array analysis five days after infection. While the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 48 publications
5
40
2
Order By: Relevance
“…At present, we have not identified a mechanistic connection between spleen size and BCWD resistance. The transcriptional response of BCWD resistant and susceptible rainbow trout homozygous clones have identified differential up-regulation of IL1 and IL10 gene transcript in susceptible clonal line B57 while complement factor C3 gene transcript showed stronger up-regulation in resistant clonal line A3 at day 5 post-challenge [54]. It will be of interest to determine whether these gene candidates are differentially expressed in our QTL population and whether they map to genomic regions with QTL detected in this study.…”
Section: Discussionmentioning
confidence: 88%
“…At present, we have not identified a mechanistic connection between spleen size and BCWD resistance. The transcriptional response of BCWD resistant and susceptible rainbow trout homozygous clones have identified differential up-regulation of IL1 and IL10 gene transcript in susceptible clonal line B57 while complement factor C3 gene transcript showed stronger up-regulation in resistant clonal line A3 at day 5 post-challenge [54]. It will be of interest to determine whether these gene candidates are differentially expressed in our QTL population and whether they map to genomic regions with QTL detected in this study.…”
Section: Discussionmentioning
confidence: 88%
“…) and Flavobacterium psychrophilum (Langevin et al. ). A single study on ISAV contradicted the pattern of enhanced response with higher microbe loads and more susceptible hosts; Workenhe et al.…”
Section: Synoptic Reviewmentioning
confidence: 99%
“…For IPNV, survivors generally elicited a stronger innate immune responses (Marjara et al 2011), whereas for IHNV, the efficiency of viral entry and strength of host down-regulation of cell transcription and translation appeared to be more important determinates of susceptibility (Miller et al 2007 and K. M. Miller, unpublished data;Purcell et al 2011). Alternately, the strength of complement activation appeared to be more predictive of resistance to bacteria A. salmonicida ( Skugor et al 2009) and Flavobacterium psychrophilum (Langevin et al 2012). A single study on ISAV contradicted the pattern of enhanced response with higher microbe loads and more susceptible hosts; Workenhe et al (2009) found that a low virulent strain of ISAV elicited a stronger host response than highly virulent strains.…”
Section: Phenotypic Variation In Disease Response Through Gene Expresmentioning
confidence: 99%
“…; Langevin et al . ). Rainbow trout skin surface constitutes a large area for possible adhesion of bacterial pathogens such as Yersinia ruckeri (Tobback et al .…”
Section: Introductionmentioning
confidence: 97%